La pedagogia 'povera': una pedagogia del reciclatge - Teixidó, Albert Esteruelas; Castillo, Xavier Laudo (Temps d'educacio, 2015)
Inspired by the Arte Povera movement that began in Italy in 1967, this paper proposes a new model for understanding education, which it describes as Povera pedagogy. A liquid pedagogy of reuse, Povera pedagogy observes the plural nature of truth in education and embraces non-planned, antidogmatic, marginal and mutative experience. Borrowing from postmodern frameworks, it focuses on the emancipation of the learner but steers clear of official, materialist and positivist pedagogies. Specifically, it refutes the dogmatism of those who situate freedom and equality as "points of arrival" in emancipatory education.